A Conceptual Examination of the Relationship between E-Leadership and Disengagement from Knowledge Sharing: A Moderated Mediated Theoretical Model - Adeniyi, Judah Inioluwa (Human Resource and Leadership Journal, 2024)
Purpose: The purpose of this conceptual paper is to develop a theoretical model to explain the relationship between e-leadership and disengagement from knowledge sharing. The current study employs the Job Demands-Resources theory (JD-R) and Adaptive Cost theory to illuminate a potential drawback of practicing e-leadership. Methodology: A comprehensive review of the existing literature on e-leadership and knowledge sharing was conducted. The synthesis of these diverse research domains led to the development of a conceptual framework that illustrates the proposed relationship between e-leadership behaviors and the tendency of individuals to disengage from knowledge-sharing activities in virtual environments. Findings. The theoretical model presented in this paper suggests that leadership in the virtual environment has the potential to cause adverse outcomes such as leader stress, which could ultimately lead them to disengage from knowledge-sharing activities in the organization. Unique contribution to theory, practice, and policy. The proposed theoretical model contributes to a deeper understanding of the complex dynamics between e-leadership and knowledge-sharing disengagement in virtual settings. By recognizing the key factors that influence disengagement, organizations can develop targeted interventions and strategies to foster a culture of knowledge sharing and enhance e-leadership effectiveness. This paper is the first study to examine how the complexities of e-leadership could negatively affect a leader's health and knowledge-sharing behavior.